The domesticity of éros and poetry in the Laws: Platonic synthesis of life and poetry - Macua Martínez, Mª Elena (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
This paper is the last part of a study which outlines the depth of poetry in Plato’s thought, suggesting that Plato’s evolution concerning the Laws (regarding the Republic), run parallel to his views on éros. From this it follows an interpretation of Plato’s last model of the city as the achievement of the frustrated longing of the poets of the former generation: a synthesis of life and poetry. Plato reaches his aim by creating a new equilibrium between the forces in tension that spur on by human desire, and by reverting to the process of demystification of the poetic language already carried out by Gorgias, in this way, at last, Platon succeeds in closing the fracture between transcendental and pragmatic poetry and merges in one and only single nature, divine and immutable, the lógos of poetry and the lógos of the law.
Keywords: Plato; Poetry; Éros.